(untitled) (Global Journals of Research in Engineering, 2020)
This project work examined power supply at Igbo-Etche Rumoukwurusi Area of Port Harcourt with the aim of improving power supply. The 33KV feeder from Elelewno substation which supplies the area was analysed using Dynamic Voltage Restorer (DVR) method. The method was used in Electrical Transient Analyzer Programme (ETAP). It was observed that load flow analysis is vital in understanding the ape rational nature of the network, by considering the following; Capacitive power, power before compensation, power after compensation, current before and after compensation, voltage drop, reactive current, supply current after compensation, losses in the distribution system and the ratio of loss without and with compensation. From the simulation there was low voltage profile and overloading of transformer along the distribution network. The voltage profile was improved by upgrading the network to standard power factor.